Efforts To Grow The Character of The Prophet's Love For Students Through Diba' Activities At As Sathi' Islamic Boarding School, Sedan District, Rembang Regency - Ida Fauziyatun Nisa’ (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
Loving the Prophet Muhammad is an obligation for all Muslims. Love for the Prophet Muhammad SAW as a source of strength in the heart and is often referred to as the power of love or the power of love. There are many verses of the Qur'an and Hadith that explain the recommendation to love the Prophet Muhammad. One way to manifest love for the Prophet Muhammad is through the reading of prayers. The purpose of this study was to find out: (1) How to Efforts to Grow the Prophet's Love Character for Santri through Diba' Activities at Al Rosyid Kendal Islamic Boarding School Dander Bojonegoro. (2) What are the Supporting and Inhibiting Factors in Efforts to Grow the Prophet's Love Character for Santri through Diba' Activities at As Sathi' Islamic Boarding School, Sedan District, Rembang Regency. To achieve the above objectives, descriptive qualitative research is used. Data collection techniques through observation, interviews, and documentation. Meanwhile, to analyze the data, the author does it by examining all the data, reducing the data, presenting the data, and concluding/verifying the data. The results showed that: the character of the love of the Prophet Muhammad SAW has been well realized in the Pondok Pesantren Putri As Sathi', Sedan sub-district, Rembang district. The realization of the love character of the Prophet Muhammad SAW has been realized in the weekly activity program for the Al Rosyid Islamic Boarding School. Efforts to grow the character of the love of the Prophet Muhammad SAW are supported by the reading of Shalawat Diba', this activity has been running since the Islamic Boarding School was founded. The implementation was on Thursday night Friday and was attended by all female students and clerics who took shelter at the Al Rosyid Islamic Boarding School. The supporting factors in an effort to grow the character of the Prophet's love are facilities and infrastructure, a relevant environment, a strong will, the right goals and intentions, encouragement and motivation. To balance it, there are also inhibiting factors, namely a long implementation time, saturation, lack of creation and innovation.